Apropriações do livro didático de literatura : um diálogo com professores e alunos - Souza, Héber Ferreira de (2015)
This research presents a work that focuses on contemporary uses of a Portuguese language and literature textbook. Having a public high school located in Cariacica/ES as its field, the research aimed at understanding how teachers and students take ownership of their Portuguese language and literature textbooks, regarding particularly to literature. The specific objectives are to know practices and representations made by High School teachers and students regarding the textbook and to outline similarities and differences between practices, representations and appropriations of teachers and students in relation to this textual support/genre. Methodologically, this research was based on a bibliography research; on a documental research as well as on a field research. In the first stage there was a survey application which was followed by the selection and analysis of theoretical texts that could be constituted as bibliographic references. In the second stage, High School teachers and students testimonies regarding the textbook were recorded through interviews and questionnaires, focusing on literature aspects. In the third stage, in the light of Roger Chartier’s theories of practices, representations and appropriations, the study of the collected and produced data was performed. In conclusion, the research intended to weave an overview concerning how this research object is currently used in the selected school. This research seems to be timely and relevant in order to establish a dialogue among contemporary movements of Graduate Programs in Literature in Brazil so as to value research and research lines that establish links with basic education.